Plano de Negócios: Drinkee - Alves, Anaílle Catalani [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Drinkee is a company created to operate on bar services sectors with professional courses, personalized consultancy services according to customer demand and providing bar’s infrastructure. In addition, the company will operate in retail selling drinks and snacks by it’s App and in the convenience store. Aiming to be a reference in the local scenario Drinkee has its first challenge according its mission: bringing a new drinking consumption experience, an innovative concept of learning and professionalization on the parties’ scene, providing quality consulting to its customers and ensuring comfort and agility on selling drinks.

A Drinkee é uma empresa criada para atuar no setor de serviços, tendo como frente cursos profissionalizantes, consultorias personalizadas de acordo com a demanda do cliente, além de disponibilizar a montagem de bares. Além disso, a empresa irá atuar no varejo, por meio da a comercialização rápida e fácil de bebidas por meio de seu aplicativo e também em sua conveniência. Visando ser referência no cenário local, a Drinkee tem seu primeiro desafio lançado por sua missão: Trazer uma nova experiência de consumo de bebidas, um conceito inovador de aprendizado e profissionalização, prestação de consultoria de qualidade aos seus clientes e trazer conforto e agilidade na comercialização de bebidas. Drinkee is a company created to operate on bar services sectors with professional courses, personalized consultancy services according to customer demand and providing bar’s infrastructure. In addition, the company will operate in retail selling drinks and snacks by it’s App and in the convenience store. Aiming to be a reference in the local scenario Drinkee has its first challenge according its mission: bringing a new drinking consumption experience, an innovative concept of learning and professionalization on the parties’ scene, providing quality consulting to its customers and ensuring comfort and agility on selling drinks.
Business Project: Drinkee
Keywords: Administração; Empreendedorismo; Negócios; Governança corporativa; Financiamento de projetos